From the Gray City to the Green City: Integrating Nature into Urban Design Through Architecture - ZULUETA CUEVA, CARLOS EDUARDO; AREVALO GARCIA, ANALIA; LA ROSA-BOGGIO, DIEGO ORLANDO; TORRES SAMILLAN, ROSA AMELIA; CUBAS RAMIREZ, CESAR EMMANUEL (LACCEI, 2025)
The accelerated growth of cities has generated environmental and social challenges due to the predominance of gray infrastructure, characterized by buildings without integration with nature, which has intensified the heat island effect, atmospheric pollution and the fragmentation of urban ecosystems. In response, architecture and urbanism have incorporated nature-based strategies to promote more sustainable and resilient urban environments. This study presents a literature review on the integration of nature in urban design through green infrastructure, addressing strategies such as green roofs and facades, ecological corridors and multifunctional urban parks, which have proven to be effective in thermal regulation, water management. and the improvement of social well-being. Through the PRISMA method, articles indexed in SCOPUS were analyzed, identifying trends, challenges and opportunities in the implementation of these solutions. The results show that, although green infrastructure offers multiple benefits, its adoption faces regulatory, economic and technical barriers. The need for an interdisciplinary approach in urban planning is emphasized, where ecology, architecture and citizen participation work together to ensure its viability. It is concluded that the transformation of cities through the integration of nature is key to facing the challenges of climate change and improving the quality of urban life through sustainable and inclusive design strategies, ensuring equity in access to natural spaces and resilience. environmental in urban development.